Molecular, morphological and chemical characterization of a poorly known lichen: the case of Ramalina wirthii (Ramalinaceae, Ascomycota) - Blázquez, Miguel; Barriopedro Peréz, Adrián; Pérez-Vargas, Israel (Mediterranean Botany, 2024)
The ascomycete genus Ramalina is one of the most remarkable examples of insular diversity and endemicity in lichen-forming fungi, as nearly half the species present in the Macaronesian region are endemic. Among the five archipelagos of the region, Azores is the one that hosts less endemic species: the fertile R. azorica and the sterile R. wirthii, both only known from the eastern islands of the archipelago. In a recent trip to the westernmost island of the Azores (Flores) we have discovered a population of R. wirthii with fertile thalli. In order to confirm the identification of these specimens, we conducted a molecular phylogenetic study based on the ITS region. In addition, we studied their morphology using 30 traits previously reported in the literature as relevant for the genus, and their secondary chemistry by thin layer chromatography. About half the morphological traits were not present in the original description of the species and are reported here for the first time. In addition, the specimens from Flores did not match with eight of the remaining characters. For this reason, they could be confused with other Ramalina species. Morphological and chemical differences with these taxa are discussed.